2022
DOI: 10.3389/fonc.2022.852718
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tryptophan and Its Main Metabolite Kynurenine and the Risk of Multiple Cancers Based on the Bidirectional Mendelian Randomization Analysis

Abstract: BackgroundTryptophan and its metabolites have been found related to various cancers, but the direction of this relationship is still unclear. The purpose of this study is to explore the causal associations of tryptophan and kynurenine with multiple cancers based on the bidirectional Mendelian randomization analysis.MethodsThe data of a genome-wide association study meta-analysis on 7,824 individuals was used to explore the genetic variants strongly associated with tryptophan and kynurenine. Genetic instruments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Tryptophan can be enzymatically hydrolyzed into kynurenine in vivo , through which to participate in cancer immune regulation ( 25 ). Our result showed that kynurenine level was downregulated in the DLC group than those of DLB and DM, while Yuzo Suzuki ( 26 ) has reported that kynurenine concentrations were significantly higher in lung cancer patients compared with the controls. Recently, Ran Li concluded that no causal relationship was found between kynurenine and lung cancers ( 27 ).…”
Section: Discussionmentioning
confidence: 48%
“…Tryptophan can be enzymatically hydrolyzed into kynurenine in vivo , through which to participate in cancer immune regulation ( 25 ). Our result showed that kynurenine level was downregulated in the DLC group than those of DLB and DM, while Yuzo Suzuki ( 26 ) has reported that kynurenine concentrations were significantly higher in lung cancer patients compared with the controls. Recently, Ran Li concluded that no causal relationship was found between kynurenine and lung cancers ( 27 ).…”
Section: Discussionmentioning
confidence: 48%
“…There are several reports on various cancers including liver cancer and the changes of tryptophan and its metabolites, but no consistent conclusions have been reached. 35,36 The main strengths of our study are its prospective design and the measurement of melatonin using liquid chromatography-tandem In conclusion, this prospective study observed that higher melatonin intake was significantly associated with a decreased risk of Abbreviations: HR, hazard ratio; T1-T3, the tertile groups of energy-adjusted melatonin intake. a Melatonin intake adjusted for total energy intake by Willett method.…”
Section: Discussionmentioning
confidence: 89%
“…Since tryptophan has other metabolic pathways, such as the kynurenine and indole pathways, other metabolites might have influenced the observed associations. There are several reports on various cancers including liver cancer and the changes of tryptophan and its metabolites, but no consistent conclusions have been reached 35,36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation